2018
DOI: 10.1038/s41423-018-0003-5
|View full text |Cite
|
Sign up to set email alerts
|

TREM-1 multimerization is essential for its activation on monocytes and neutrophils

Abstract: The triggering receptor expressed on myeloid cells-1 (TREM-1) is a receptor expressed on innate immune cells. By promoting the amplification of inflammatory signals that are initially triggered by Toll-like receptors (TLRs), TREM-1 has been characterized as a major player in the pathophysiology of acute and chronic inflammatory diseases, such as septic shock, myocardial infarction, atherosclerosis, and inflammatory bowel diseases. However, the molecular events leading to the activation of TREM-1 in innate immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 43 publications
4
65
0
2
Order By: Relevance
“…Monocytes also express TREM‐1, the level of which increases upon stimulation with LPS . LR12 dose‐dependently reduced TG supported by monocytes, in both unstimulated and stimulated cells (Figure A‐C).…”
Section: Resultsmentioning
confidence: 79%
“…Monocytes also express TREM‐1, the level of which increases upon stimulation with LPS . LR12 dose‐dependently reduced TG supported by monocytes, in both unstimulated and stimulated cells (Figure A‐C).…”
Section: Resultsmentioning
confidence: 79%
“…However, myricetin treatment abrogated the increase levels of TREM-1 gene and protein expression (Figures 7A-D). Activation of TREM-1 has been shown to trigger and aggravate inflammation, especially through synergism with TLRs signaling (13)(14)(15)(16); therefore, we further assessed the effects of myricetin on the mRNA expression of TLR2, TLR4, and its adapter protein MyD88. As expected, our result confirmed that myricetin treatment significantly inhibited TLR2/4-MyD88 signaling expression in livers from NASH mice.…”
Section: Discussionmentioning
confidence: 99%
“…The triggering receptor expressed on myeloid cells (TREM)-1 is a kind of immunoglobulin superfamily activation receptors express on neutrophils and monocyte macrophages (13,14). Upon activation, TREM-1 can trigger and augment inflammatory reaction, especially through synergism with toll-like receptors (TLRs) signaling in macrophages (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LR-12 is shown to block TREM-1 and reduces its activation of monocyte/macrophage to form foam cells in atherosclerosis pathogenesis 67,95 . Furthermore, recently been found the multimerization of TREM-1 that causes its activation is inhibited by LR12 96 . Also, curcumin extracted from yellow pigment of turmeric has been shown to inhibit TREM-1 down streaming signaling.…”
Section: Therapeutics Of Cardiovascular Diseases Targeting Trem1 Pathwaymentioning
confidence: 99%